Effectiveness of humor training among adolescents with autism. (30th December 2016) - Wu, Ching-Lin; Liu, Ya-Ru; Kuo, Ching-Chih; Chen, Hsueh-Chih; Chang, Yu-Lin
Abstract: Humor training has been applied to educational and clinical cases and has been found to be effective, but humor training for individuals with autism is relatively rare. The present study proposed a humor-knowledge and humor-skill training workshop to enhance the humor comprehension and appreciation of individuals with autism and examined the effects of the training. Participants were 20 adolescents with autism and average intelligence (above 70 in WAIS-III). They were randomly divided into experimental and control groups. Both questionnaire of joke comprehension and appreciation and a humor style questionnaire were used as instruments. The results supported the effectiveness of the 15-h training. The comprehension and appreciation of nonsense humor were significantly increased in the experimental group in comparison with the control group, although the incongruity-resolution jokes remained difficult to comprehend. The tendency to use affiliative humor was greater among individuals with autism in the experimental group, suggesting that the appreciation of humor can be learned.